Microbiota Associated With Cholesteatoma Tissue in Chronic Suppurative Otitis Media - Frank, Daniel N.; Magno, Jose Pedrito M.; Velasco, Karen Joyce S.; Bootpetch, Tori C.; Salud, Jacob Ephraim D.; David, Kevin Jer V.; Miller, Aaron L.; Yee, Eljohn C.; Dulnuan, Heather P.; Pyles, Richard B.; Lacuata, Jan Alexeis C.; Arbizo, Jeric L.; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Otitis media (OM), defined as infection or inflammation of the middle ear (ME), remains a major public health problem worldwide. Cholesteatoma is a non-cancerous, cyst-like lesion in the ME that may be acquired due to chronic OM and cause disabling complications. Surgery is required for treatment, with high rates of recurrence. Current antibiotic treatments have been largely targeted to previous culturable bacteria, which may lead to antibiotic resistance or treatment failures. For this study, our goal was to determine the microbiota of cholesteatoma tissue in comparison with other ME tissues in patients with long-standing chronic OM. ME samples including cholesteatoma, granulation tissue, ME mucosa and discharge were collected from patients undergoing tympanomastoidectomy surgery for chronic OM. Bacteria were profiled by 16S rRNA gene sequencing in 103 ME samples from 53 patients. Respiratory viruses were also screened in 115 specimens from 45 patients. Differences in bacterial profiles (beta-diversity) and the relative abundances of individual taxa were observed between cholesteatoma and ME sample-types. Additionally, patient age was associated with differences in overall microbiota composition while numerous individual taxa were differentially abundant across age quartiles. No viruses were identified in screened ME samples. Biodiversity was moderately lower in cholesteatoma and ME discharge compared to ME mucosal tissues. We also present overall bacterial profiles of ME tissues by sample-type, age, cholesteatoma diagnosis and quinolone use, including prevalent bacterial taxa. Our findings will be useful for fine-tuning treatment protocols for cholesteatoma and chronic OM in settings with limited health care resources.